2016
DOI: 10.1038/mt.2015.134
|View full text |Cite
|
Sign up to set email alerts
|

Development of Patient-specific AAV Vectors After Neutralizing Antibody Selection for Enhanced Muscle Gene Transfer

Abstract: A major hindrance in gene therapy trials with adeno-associated virus (AAV) vectors is the presence of neutralizing antibodies (NAbs) that inhibit AAV transduction. In this study, we used directed evolution techniques in vitro and in mouse muscle to select novel NAb escape AAV chimeric capsid mutants in the presence of individual patient serum. AAV mutants isolated in vitro escaped broad patient-specific NAb activity but had poor transduction ability in vivo. AAV mutants isolated in vivo had enhanced NAb evasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 62 publications
1
33
0
Order By: Relevance
“…The imaging was carried out by the IVIS Lumina In Vivo imaging system and the photon signal was measured by Living Image software. The results were shown in Figure 2 of the original paper (Li et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging was carried out by the IVIS Lumina In Vivo imaging system and the photon signal was measured by Living Image software. The results were shown in Figure 2 of the original paper (Li et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Clone the capsids from DNA shuffling library into wild-type AAV2 plasmid psub201 to generate AAV capsid DNA library (Li et al ., 2008; Li et al ., 2016). …”
Section: Methodsmentioning
confidence: 99%
“…50 AAV serotype switching and capsid engineering strategies have produced promising results. 51,52 Because the capsid composition is different between rAAV RD and rAAV HD particles, it can be hypothesized that humoral immunity may also have some difference. Immunoelectron microscopy studies indicated that rAAV RD and rAAV…”
Section: Discussionmentioning
confidence: 99%
“…This approach has allowed isolation of neutralizing antibody escaping AAV variants AAV-r2.15 by Maheshri et al and AAV-DJ by Grimm et al [127,128]. More recently, Li et al found that capsid variants isolated following in vitro selection in human serum had poor in vivo transduction strength although they were able to escape neutralization [129]. In vivo selection in the presence of the patient serum may yield escaping-capsids with better in vivo performance [129].…”
Section: Re-engineering Aav For Improved Systemic Deliverymentioning
confidence: 99%